(untitled) (Conferencea, 2022)
The article studies an important component of the effective development of modern Russian society is the state youth policy aimed at creating conditions for young people to realize the possibilities of building their future and the future of the country. The key objective of such a policy "is to educate patriotic youth with independent thinking, with a creative worldview, professional knowledge, demonstrating a high culture, including a culture of interethnic communication, responsibility and the ability to make independent decisions aimed at improving the welfare of the country, people and their families"